2021
DOI: 10.1371/journal.pone.0246122
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae carriage and antibiotic susceptibility among Indonesian pilgrims during the Hajj pilgrimage in 2015

Abstract: The Hajj is an annual pilgrimage to Mecca and one of the largest gathering of people in the world. Most Indonesian pilgrims are senior adults and elderly adults, who are more prone to acquire infections during the Hajj ritual. The aims of this study are to investigate the dynamics of Streptococcus pneumoniae colonization and to investigate antibiotic susceptibility of pneumococcal strains in Indonesian pilgrims. This was a prospective multi-site longitudinal study in Indonesian hajj pilgrims aged >18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…In addition, one non-typeable isolate displayed resistance to penicillin, ampicillin, and amoxicillin/amoxicillin-clavulanic acid. Similar results were widely published before [ 7 , 11 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, one non-typeable isolate displayed resistance to penicillin, ampicillin, and amoxicillin/amoxicillin-clavulanic acid. Similar results were widely published before [ 7 , 11 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…in 17 studies [ 28 , 30 , 33 , 36 , 37 , 42 , 43 , 48 , 52 , 55 , 57 , 61 , 63 , 64 , 67 , 68 , 69 ], Streptococcus spp. in seven study [ 33 , 42 , 65 , 70 , 71 , 72 , 73 ], Neisseria meningitidis in three studies [ 21 , 22 , 54 ], Haemophilus influenzae was reported in two studies [ 27 , 32 ], Mycobacterium tuberculosis in two studies [ 74 , 75 ], and Stenotrophomonas maltophilia in one study [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The serotype-negative isolates were confirmed by real-time PCR targeting lytA to confirm that the isolates were S. pneumoniae . Isolates with positive lytA were assigned as non-typeable S. pneumoniae by PCR [ 28, 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Serotype determination was performed by sequential multiplex conventional PCR, targeting the wzy gene (a component of the pneumococcal capsular locus) and consisted of eight reactions as described previously [27,28]. A master mix for each reaction (25 µl) was made by adding PCR H 2 O, 0.5 µl of 5×PCR buffer (Promega), 3.5 µl of 25 mm magnesium chloride (MgCl 2 ), 1 µl of 5 mm dNTPs (Promega), varied volumes of 25 µm forward primer and 25 µm reverse primer, 0.2 µl Taq Polymerase 2U, and 2.5 µl DNA template into a 1.5 ml microcentrifuge tube.…”
Section: S Pneumoniae Culture and Identificationmentioning
confidence: 99%